Voxel-based mapping of grey matter volume and glucose metabolism profiles in amyotrophic lateral sclerosis - Buhour, M-S. (EJNMMI Res, 2017)
BACKGROUND: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive disease of the nervous system involving both upper and lower motor neurons. The patterns of structural and metabolic brain alterations are still unclear. Several studies using anatomical MRI yielded a number of discrepancies in their results, and a few PET studies investigated the effect of ALS on cerebral glucose metabolism. The aim of this study was threefold: to highlight the patterns of grey matter (GM) atrophy, hypometabolism and hypermetabolism in patients with ALS, then to understand the neurobehavioral significance of hypermetabolism and, finally, to investigate the regional differences between the morphologic and functional changes in ALS patients, using a specially designed voxel-based method. Thirty-seven patients with ALS and 37 age- and sex-matched healthy individuals underwent both structural MRI and (18)[F]-fluorodeoxyglucose (FDG) PET examinations. PET data were corrected for partial volume effects. Structural and metabolic abnormalities were examined in ALS patients compared with control subjects using two-sample t tests in statistical parametric mapping (SPM). Then, we extracted the metabolic values of clusters presenting hypermetabolism to correlate with selected cognitive scores. Finally, GM atrophy and hypometabolism patterns were directly compared with a one-paired t test in SPM. RESULTS: We found GM atrophy as well as hypometabolism in motor and extra motor regions and hypermetabolism in medial temporal lobe and cerebellum. We observed negative correlations between the metabolism of the right and left parahippocampal gyri and episodic memory and between the metabolism of right temporal pole and cognitive theory of mind. GM atrophy predominated in the temporal pole, left hippocampus and right thalamus, while hypometabolism predominated in a single cluster in the left frontal superior medial cortex. CONCLUSIONS: Our findings provide direct evidence of regional variations in the hierarchy and relationships between GM atrophy and hypometabolism in ALS. Moreover, the (18)FDG-PET investigation suggests that cerebral hypermetabolism is deleterious to cognitive function in ALS.